Measuring Business Incubation Performance in the ICT Industry in Malaysia - Abdul Khalid, Fararishah; Gilbert, David; Huq, Afreen (2013)
Incubator-incubation impact studies emerged in the 1990s to uncover the effectiveness of incubation programs in various set-ups. Researchers investigated the impacts of business incubation on the survival rates of incubatees and found that the age of the incubator, and knowledge accumulated and disseminated by the incubator over time are the most important variables for new incubating ventures. It is evident that the evaluation of business incubation performance is ever evolving and still fragmented especially in developing countries. Research has investigated the relationship between incubatee performance of high- and low-growth tech firms and incubator characteristics including size, location, and type of incubator. Subsequently, incubation impacts are surprisingly understudied and represent fertile ground for future research. postulated good performance of business incubators helps an economy to attain its macroeconomic targets through promoting economic growth and increased employment. In Malaysia, there has been little study conducted on business incubators focusing on performance measures of the incubators and incubatees. This paper examines the indicators used by ICT incubators in Malaysia to measure their performance and their incubatees’ performance. A mixed-methods approach was adopted for this research consisting of 118 incubatees and 6 incubator managers. The results revealed that there is a wide range of measurements adopted by the incubators caused by different objectives and motivations of the incubators.